New Insights Into Sperm Ultrastructure Through Enhanced Scanning Electron Microscopy - Korneev, Denis; Merriner, D. Jo; Gervinskas, Gediminas; de Marco, Alex; O’Bryan, Moira K. (Frontiers in Cell and Developmental Biology, 2021)
The analysis of spermatozoa morphology is fundamental to understand male fertility and the etiology of infertility. Traditionally scanning electron microscopy (SEM) has been used to define surface topology. Recently, however, it has become a critical tool for three-dimensional analysis of internal cellular ultrastructure. Modern SEM provides nanometer-scale resolution, but the meaningfulness of such information is proportional to the quality of the sample preservation. In this study, we demonstrate that sperm quickly and robustly adhere to gold-coated surfaces. Leveraging this property, we developed three step-by-step protocols fulfilling different needs for sperm imaging: chemically fixed monolayers for SEM examination of the external morphology, and two high-pressure freezing-based protocols for fast SEM examination of full cell internal morphology and focused ion-beam SEM (FIB-SEM) tomography. These analyses allow previously unappreciated insights into mouse sperm ultrastructure, including the identification of novel structures within the fibrous sheath and domain-specific interactions between the plasma membrane and exosome-like structures.